Evaluation of mental health first aid training in a diverse community setting. (12th July 2012) - Morawska, Alina; Fletcher, Renee; Pope, Susan; Heathwood, Ellen; Anderson, Emily; McAuliffe, Christine
ABSTRACT: Mental health first aid (MHFA) training has been disseminated in the community and has yielded positive outcomes in terms of increasing help‐seeking behaviour and mental health literacy. However, there has been limited research investigating the effectiveness of this programme in multicultural communities. Given the increasing levels of multiculturalism in many countries, as well as the large number of barriers presented to these groups when trying to seek help for mental illnesses, the present study aimed to investigate the effectiveness of MHFA in these settings. A total of 458 participants, who were recruited from multicultural organizations, participated in a series of MHFA training courses. Participants completed questionnaires pre and post the training course, and 6‐month follow‐up interviews were conducted with a subsample of participants. Findings suggested that MHFA training increased participant recognition of mental illnesses, concordance with primary care physicians about treatments, confidence in providing first aid, actual help provided to others, and a reduction in stigmatizing attitudes. A 6‐month follow up also yielded positive long‐term effects of MHFA. The results have implications for further dissemination and the use of MHFA in diverse communities. In addition, the results highlight the need for mental health training in health‐care service providers.